1997
DOI: 10.2134/agronj1997.00021962008900060007x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Straw Mulching of Irrigation Furrows: Soil Erosion and Nutrient Losses

Abstract: There is widespread concern about loss of sediments, NO‐3, and phosphate into surface water from irrigated farmlands. We studied the effects of 900 kg ha−1 wheat (Triticum spp.) straw, mechanically applied to irrigation furrows, on sediments and on N and P losses in the runoff. The field was on a Nyssa silt loam soil (coarse‐silty, mixed, mesic Xerollic Haplodurid) with 3% slope planted to onion (Allium cepa L.), and received 0, 50, or 200 kg P ha−1 incorporated to 0.1 m deep. Furrows were side‐dressed with 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Uncontrolled runoff and sediment transport can carry large amounts of non-point source pollutants (e.g., fertilizers, pesticides, and herbicides) to downstream waters. Shock et al (1997) observed that application of 0.90 Mg ha −1 of wheat straw to irrigated furrows reduced cumulative sediment loss from 333 to 17 Mg ha −1 after 17 irrigations, total N lost from 230 to 33 kg ha −1 in the first 6 irrigations, and total P lost from 215 to 18 kg ha −1 after 6 irrigations. Maintaining crop residue cover also significantly reduces losses of NO 3 -N, NH 4 -N, and PO 4 -P in runoff (Torbert et al, 1999).…”
Section: Runoff and Soil Lossmentioning
confidence: 93%
“…Uncontrolled runoff and sediment transport can carry large amounts of non-point source pollutants (e.g., fertilizers, pesticides, and herbicides) to downstream waters. Shock et al (1997) observed that application of 0.90 Mg ha −1 of wheat straw to irrigated furrows reduced cumulative sediment loss from 333 to 17 Mg ha −1 after 17 irrigations, total N lost from 230 to 33 kg ha −1 in the first 6 irrigations, and total P lost from 215 to 18 kg ha −1 after 6 irrigations. Maintaining crop residue cover also significantly reduces losses of NO 3 -N, NH 4 -N, and PO 4 -P in runoff (Torbert et al, 1999).…”
Section: Runoff and Soil Lossmentioning
confidence: 93%
“…Use of mulches in perturbed areas protects the soil and reduces water and nutrient losses (Paris et al 1998;Rathore 1998;Shock et al 1997). On the other hand, the mulches increase both the decomposition rate and the nutrient concentration in the soil (Cogle et al 1997;Yohannes 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Soil is typically tilled several times before planting, leaving little residue (Swanton et al, 2004;Mitchell et al, 2014). This may increase water runoff and nutrient losses, leading to soil degradation and water pollution (Shock et al, 1991(Shock et al, , 1997. As a result, the soil surface remains virtually unprotected from wind (Zobeck et al, 2000).…”
Section: Potato and Onion Farming As Prime Examples Of Highinput Intementioning
confidence: 99%